Patterns of alcohol use between genders: A cross-cultural evaluation - Kerr-Correa, Florence; Igami, Thais Zamudio; Hiroce, Vivian; Tucci, Adriana Marcassa (Elsevier B.V., 2007)
Introduction: Alcohol use by men and women is very much influenced by social habits and customs. Cultural peculiarities and biological differences between the sexes require more focused and standardized studies. The objective was to systematize information on patterns of alcohol use between the sexes.Method: A literary review (1972-2004) identified 96 publications (Lilacs, Scielo, Medline) and some related books.Results and conclusions: Men drank more and presented more problems (legal, family, social, clinical, traumas and mortality) associated with alcohol use; the consequences of alcohol use in developing countries with low death rates is even higher. Women can face more discrimination by using alcohol as well as worse health problems when they abuse drinking (liver, pancreas, and central and peripheral nervous system problems, psychiatric comorbidity, etc.); sexual abuse is more commonly associated with women than discussing the different responses to treatment. As for social roles/responsibilities exercised by women, there are indications that marriage, employment, and children have a good influence, discouraging alcohol use, while divorce, unemployment, and no children contribute to higher consumption. For both sexes, religion was a protective factor for alcohol use; acculturation was a strong influence in the pattern of alcohol use, and alcohol worsened the evolution of existing psychiatric disorders. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: gender; alcohol; patterns of alcohol use; review